Attitudes of Secondary School Students to the Basic Sciences in Selected Local Government Areas of Oyo state. - Alao, Emmanuel Oluyemi (Obafemi Awolowo University, 2014)
This study examined the attitudes of Oyo State secondary school students to the basic sciences, namely, Physics, Chemistry and Biology and also the relationship between their attitudes and their achievements in these science subjects. Six hypotheses were generated for the study. The hypotheses were tested at 0.01 level of significance.